Negative life events and the risk of depression: Findings from Indonesia Family Life Survey 2014/2015 - Irmansyah Irmansyah; Ida Ayu Mas Amelia Kusumaningtyas; Aryana Satrya; Laura Anselmi; Jonathan Gibson; Jack Wilkinson; Sri Idaiani; Budi Anna Keliat; Dwidjo Susilo; Hasbullah Thabrany; Herni Susanti; Helen Brooks; et al. (PLoS ONE, 2026)
Background Negative life experiences are well-established risk factors for mental health problems, yet evidence from low- and middle-income countries remains limited. Many studies also overlook area-level factors that may influence these relationships. This study aimed to examine the association between negative life events and depression among individuals in Indonesia, accounting for both individual and area-level characteristics. Methods This cross-sectional study used data from 31,446 individuals aged 15 years and older who participated in the Indonesia Family Life Survey Wave 5 (IFLS-5), conducted in 2014–2015. Depression was assessed using the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10), a validated instrument measuring depressive symptoms during the past week. Negative life events, including chronic illness (self or family member), natural disasters or accidents, and deaths of family members within the past year, were evaluated. Multilevel logistic regressions accounted for the hierarchical data structure and adjusted for demographic, socioeconomic, behavioural, and district-level characteristics. Results The prevalence of depression was 23%. Experiencing one negative life event increased the odds of depression (adjusted odds ratio [AOR] = 1.22, 95% confidence interval [CI]: 1.15–1.30), while two or more events further elevated the odds (AOR = 1.55, 95% CI: 1.32–1.83), adjusted for covariates. Individually, chronic illness (AOR = 1.25, 95% CI: 1.17–1.33), natural disasters or accidents (AOR = 1.41, 95% CI: 1.15–1.73), and deaths of family members (AOR = 1.14, 95% CI: 1.03–1.26) were significantly associated with depression. Conclusion Multiple and specific negative life events substantially increase the risk of depression among Indonesians. These findings highlight the importance of integrating culturally sensitive mental health interventions within community and healthcare settings.